Testing the Relationship Between Teachers’ Epistemological Beliefs (EB) and a Faculty’s School Growth Mindset: Inter-cultural Comparison of EB Between East and West (Journal of Organizational Psychology, 2020)
This study compared elementary and middle school educators’ (n=243) epistemological beliefs (EB) between western (southwestern US) and eastern (Asian) contexts. Results suggested contextual and cultural elements influence the development of teachers’ individual EB factors of Certainty Knowledge and Learning/Effort Process. Innate/Fixed Ability and Criticizing Authority factors remained stable between cultures. EB dimensions showed stability across demographic characteristics of gender, total years teaching, position, and education level. Teachers’ self-reports of their Innate/Fixed Ability showed a correlation (r = .23) with their perceptions of their school’s growth mindset. A broad review of the literature and implications are provided.
Keywords: Organizational Psychology; epistemology; pedagogy; development; teachers and administrators; growth mindset; eastern and western contexts; elementary and middle schools